2020
DOI: 10.1093/carcin/bgaa084
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits intestinal tumorigenesis through inhibiting wnt signaling

Abstract: Artesunate (ART) is a clinically approved antimalarial drug and was revealed as a candidate  of colorectal cancer chemopreventive agents in our drug screening system. Here, we aimed to understand the suppressive effects of ART on intestinal tumorigenesis. In vitro, ART reduced T-cell factor/lymphoid enhancer factor (TCF/LEF) promoter transcriptional activity. In vivo, ART inhibited intestinal polyp development. We found that ART reduces TCF1/TCF7 nuclear translocation by binding the Ras-related nuclear protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Both c-Myc and Cyclin D1 are cell proliferation-related factors that are induced by activation of Wnt signaling through APC gene mutations found in ~ 80% of CRC (21,22). So far, it has been suggested that suppression of excessive Wnt signaling is involved in polyp inhibition experiments using Min mice (23)(24)(25). Previous studies reported that aspirin suppressed the expression levels of c-Myc and Cyclin D1 in many cancer cells and also suppressed cell proliferationrelated marker proteins, such as Ki67 and PCNA (26-28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both c-Myc and Cyclin D1 are cell proliferation-related factors that are induced by activation of Wnt signaling through APC gene mutations found in ~ 80% of CRC (21,22). So far, it has been suggested that suppression of excessive Wnt signaling is involved in polyp inhibition experiments using Min mice (23)(24)(25). Previous studies reported that aspirin suppressed the expression levels of c-Myc and Cyclin D1 in many cancer cells and also suppressed cell proliferationrelated marker proteins, such as Ki67 and PCNA (26-28).…”
Section: Discussionmentioning
confidence: 99%
“…The other regions were opened longitudinally and xed at between sheets of lter paper in 10% buffered formalin. Polyp number, size, and intestinal distributions were assessed using a stereoscopic microscope (23). All experiments were performed in accordance with the "Guidelines for Animal Experiments in the National Cancer Center" and were approved by the Institutional Ethics Review Committee for Animal Experimentation of the National Cancer Center.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both c-Myc and Cyclin D1 are cell proliferation-related factors that are induced by activation of Wnt signaling through APC gene mutations found in ~ 80% of CRC 21 , 22 . So far, it has been suggested that suppression of excessive Wnt signaling is involved in polyp inhibition experiments using Min mice 23 25 . Previous studies reported that aspirin suppressed the expression levels of c-Myc and Cyclin D1 in many cancer cells and also suppressed cell proliferation-related marker proteins, such as Ki67 and PCNA 26 28 .…”
Section: Discussionmentioning
confidence: 99%